Urban sustainability in the Arctic : measuring progress in circumpolar cities - Orttung, Robert W. (Studies in the Circumpolar North, 2020)
"Urban Sustainability in the Arctic advances our understanding of cities in the far north by applying elements of the international standard for urban sustainability (ISO 37120) to numerous Arctic cities. In delivering rich material about northern cities in Alaska, Canada, and Russia, the book examines how well the ISO 37120 measures sustainability and how well it applies in northern conditions. In doing so, it links the Arctic cities into a broader conversation about urban sustainability more generally"--